Insights into electrophysiological mechanisms of atrial fibrillation propagation using simultaneous bi-atrial mapping. (24th May 2021) - Pope, M; Kuklik, P; Banerjee, A; Briosa E Gala, A; Leo, M; Mahmoudi, M; Paisey, J; Betts, TIMOTH
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Oxford Biomedical Research Centre Introduction: Early evidence of pulmonary vein triggers initiating AF has led to focus on the left atrium (LA). Little work has been done to characterise the role of the right atrium (RA) in AF maintenance. Purpose: To characterise the relative roles of the LA and RA in maintenance of atrial fibrillation and explore mechanisms of AF propagation. Methods: Simultaneous bi-atrial mapping was carried out in patients undergoing first time catheter ablation using 2 linked non-contact charge density mapping systems to obtain 30-second recordings during AF. The predominant channel of communication between chambers was identified and the time difference across this channel measured (see figure). The proportion of signals earlier in each chamber was calculated and a dominant chamber identified if preceding the opposite chamber for ≥60% of the recording. AF was characterised in each chamber according to frequency of specific propagation patterns (localised rotational activation (LRA) and focal firing (FF)). The difference in AF characteristics in the LA and RA according to acute procedural outcome (termination with ablation vs. DCCV) was measured using 2-way ANOVA and predictors of AF termination identified using binomial logistic regression. Results: Twenty-one patients were included (16 persistent AF, 5 paroxysmal AF, 11 in sinus rhythm at baseline) with 41 maps obtained prior to ablation. A dominant chamber was identified in 11 maps (in 9 patients). Of these, 5 maps (in 4 patients) were LA dominant, and 6 maps (in 5 patients) were RA dominant. The remainder showed balanced interatrial propagation. For patients with persistent AF, in the RA, those needing DCCV had more LRA than those with termination with ablation (79 activations, (95% CI 65-93) vs. 51 (30-71); p = 0.025). There was no difference in the LA in the two groups (77 vs 59, p = 0.541). There were fewer FFs in the RA vs LA in patients needing DCCV (123 (106-140) vs. 155 (137-172), p = 0.012)(see panel F). No differences in distribution of LIA were observed. The frequency of LRA (p = 0.003) and FF (p = 0.004) in the RA, and RA AFCL (p = 0.041), were predictors of acute procedural outcome. Conclusions: Our novel approach of simultaneous bi-atrial mapping revealed that mechanisms responsible for AF maintenance were evenly distributed between atria whilst acute AF termination with left atrial ablation was dependent on the contribution of right atrial substrate. Strategies incorporating right atrial mechanisms may result in improved outcomes from AF ablation.